2004
DOI: 10.1104/pp.104.039255
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Membrane Depolarization Induced by Abscisic Acid in Arabidopsis Suspension Cells Involves Reduction of Proton Pumping in Addition to Anion Channel Activation, Which Are Both Ca2+ Dependent

Abstract: In Arabidopsis suspension cells a rapid plasma membrane depolarization is triggered by abscisic acid (ABA). Activation of anion channels was shown to be a component leading to this ABA-induced plasma membrane depolarization. Using experiments employing combined voltage clamping, continuous measurement of extracellular pH, we examined whether plasma membrane H 1 -ATPases could also be involved in the depolarization. We found that ABA causes simultaneously cell depolarization and medium alkalinization, the secon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
70
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 96 publications
(82 citation statements)
references
References 83 publications
12
70
0
Order By: Relevance
“…Other findings have shown that monoterpenes affect biological membranes by damaging their structure and changing their lipid packing density, resulting in increasing ion permeability and perturbs membrane-bound enzyme function [54]. This is similar to the effect of abscisic acid on Arabidopsis cells leading to abscission [55].…”
Section: Stress Senescence and The Role Of Vtcssupporting
confidence: 58%
“…Other findings have shown that monoterpenes affect biological membranes by damaging their structure and changing their lipid packing density, resulting in increasing ion permeability and perturbs membrane-bound enzyme function [54]. This is similar to the effect of abscisic acid on Arabidopsis cells leading to abscission [55].…”
Section: Stress Senescence and The Role Of Vtcssupporting
confidence: 58%
“…Here, we focused on the activation of anion channels essential for the ABA-induced depolarization that initiates ion efflux from guard cells, and finally leads to stomatal closure. In addition, deactivation of H ϩ -ATPases may contribute to the depolarization, as was recently shown for suspension cells of Arabidopsis thaliana (43). Although ABA inhibition of H ϩ -ATPases was also reported for guard cells (44), the changes in H ϩ current (45) will be masked by the massive increase in anion channel activity recorded for guard cells in intact plants.…”
Section: Discussionmentioning
confidence: 84%
“…There are many reports in the literature concerning the impairment of the transport ATPases through interactions with ROS either through the direct oxidation of amino acid residues or via the peroxidation of membrane phospholipids (reviewed in Kourie 1998). It is also possible that ROS-induced cytosol Ca 2+ elevations (reviewed in Mori and Schroeder 2004), in turn, can inhibit PM H + -ATPase activity (Brault et al 2004;Kinoshita et al 1995;Polevoi et al 1996), and depolarise plasma membrane potential (Trouverie et al 2008). It can be also speculated that the inhibition of IAA-induced growth may also be caused by an ROS-induced K + efflux, which results in a dramatic K + loss from plant cells (reviewed in Demidchik et al 2014).…”
Section: Discussionmentioning
confidence: 99%